Hepatocellular carcinoma as a complication of Niemann‐Pick disease type C1. Issue 10 (17th June 2021) - Rodriguez‐Gil, Jorge L.; Bianconi, Simona E.; Farhat, Nicole; Kleiner, David E.; Nelson, Marie; Porter, Forbes D.
ABSTRACT: Niemann‐Pick disease type C (NPC) is a rare and fatal lysosomal storage disorder characterized by neurodegeneration and hepatic involvement. Mutations in either NPC1 or NPC2, two genes encoding lysosomal proteins, lead to an intracellular accumulation of unesterified cholesterol and sphingolipids in late endosomes/lysosomes. Early cholestatic disease is considered a hallmark of patients with early disease onset. This can potentially result in liver failure shortly after birth or subclinical hepatic inflammation. Previous reports suggest an association between NPC and hepatocellular carcinoma, a cancer that is rare during childhood. We present a 12‐year‐old male with a known diagnosis of NPC1 disease who was found to have a stage III hepatocellular carcinoma, underwent surgical resection with adjuvant chemotherapy, and subsequently died from metastatic disease. This report provides evidence of an increased risk of hepatocellular carcinoma in NPC patients, suggesting a need for screening in this patient population.